2023
DOI: 10.3390/ijms24054410
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Fingerprint of Lung Fibrosis Progression and Response to Therapy in Bleomycin-Induced Mouse Model

Abstract: Idiopathic pulmonary fibrosis (IPF) is a chronic lung disease characterized by the aberrant accumulation of extracellular matrix in the lungs. nintedanib is one of the two FDA-approved drugs for IPF treatment; however, the exact pathophysiological mechanisms of fibrosis progression and response to therapy are still poorly understood. In this work, the molecular fingerprint of fibrosis progression and response to nintedanib treatment have been investigated by mass spectrometry-based bottom-up proteomics in para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 68 publications
0
3
0
Order By: Relevance
“…The major IPF experimental model is bleomycin-treated C57bl6 mice [ 12 , 25 , 26 ]. However, these animals develop acute fibrosis, which leads to self-healing 21 days post-instillation (p.i.)…”
Section: Resultsmentioning
confidence: 99%
“…The major IPF experimental model is bleomycin-treated C57bl6 mice [ 12 , 25 , 26 ]. However, these animals develop acute fibrosis, which leads to self-healing 21 days post-instillation (p.i.)…”
Section: Resultsmentioning
confidence: 99%
“…CCT8, a subunit of the cytoplasmic chaperonin containing TCP1 complex (CCT), is necessary for correct folding of many proteins. Recent experimental studies have shown that overexpression of CCT8 not only promotes EMT, but also involved in lung brosis development and progression (34,40). Thus, up-regulation of CCT8 in the TBBx of LTx patients with EOS and ACR may be an important clinical indicator for the development of brosis and graft rejection in these cases.…”
Section: Discussionmentioning
confidence: 99%
“…Coro1A, also known as translational activator of cytochrome oxidase, regulates various cellular processes such as migration and endocytosis. Coro1A overexpression is signi cantly correlated with in ammatory processes, oxidative stress and the progression of lung brosis (40,41). Recent evidence has revealed higher expression of Coro1A in brotic tissues than normal cells, and that Coro1A expression level was directly related to brosis severity (42).…”
Section: Discussionmentioning
confidence: 99%
“…To perform protein identification and quantification, a pool of 6 slices of BFPE and FFPE renal samples at three different fixation time points (2, 12, and 24 h), along with a pool of 5 slices of BFPE and FFPE renal amyloidosis, were collected and prepared for nLC-ESI MS/MS analysis. Samples were deparaffinized and digested as already described . After the paraffin removal, antigen retrieval, and trypsinization, the enzymatic reaction was stopped by adding TFA to a final concentration of 0.5% to reach an acidic pH (<2).…”
Section: Methodsmentioning
confidence: 99%